Cobalt Nanoparticles Formed upon Reaction of Cp*Co(III) Metallacycles with Na[BHEt3] Show Catalytic Activity in the Hydrosilylation of Aryl Ketones, Aldehydes and Nitriles. Issue 6 (21st December 2022) - Antuña‐Hörlein, Carmen; Wu, Fule; Deraedt, Christophe; Bouillet, Corinne; Djukic, Jean‐Pierre
Abstract: The reactivity of the 2‐phenylpyridine‐derived [Cp*CoI(phpy‐ κ C, N )] metallacycle towards Et3 SiH and hydrides was evaluated. The treatment of the same Co(III) complex with Na[BHEt3 ] resulted in its decomposition into cobalt nanoparticles. The hydride‐promoted decomposition of the metallacycle involves the transient formation of an elusive hydrido‐cobalt(III) intermediate, the traces of which were detected by 1 H NMR spectroscopy at sub‐ambient temperature. The Co nanoparticles produced from a 5 mol% and 10 mol% load of cobaltacycle and Na[BHEt3 ] respectively contain Co(0) that is responsible for the hydrosilylation by Et3 SiH of arylketones into silylalkyl ethers. To minimize the residual side reduction of carbonyls by Na[BHEt3 ], a mixture of 5 mol% of the latter with 5 mol% of BEt3 was found to produce optimal hydrosilylation yields at 40 °C in 2 h. Under similar conditions, several arylnitriles were mono‐hydrosilylated into N‐silyl‐imines in yields ranging from 68 to 100 %. Abstract : The treatment of a cobaltacycle with Na[BHEt3 ] produces Co nanoparticles that are active as catalyst for the hydrosilylation of aromatic aldehydes, ketones and nitriles.